RCM-Based Maintenance Strategy for Coating Machine Downtime Reductione - Yeriko Holman Oktavianus; Siti Rahayu; Andini Putri Riandani (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2026)
The coating machine plays a critical role in pharmaceutical production because it affects coating uniformity, drying stability, product quality, and production continuity. However, maintenance studies on pharmaceutical coating machines are still limited, especially those that integrate reliability indicators, downtime dominance analysis, failure risk assessment, root cause analysis, and RCM decision logic into one structured maintenance framework. This study proposes an integrated RCM-based reliability decision framework to identify critical components and formulate maintenance priorities for reducing coating machine downtime at PT. Triyasa Nagamas Farma. The framework combines Mean Time Between Failure (MTBF), Mean Time to Repair (MTTR), Availability, Pareto analysis, Failure Mode and Effect Analysis (FMEA), Risk Priority Number (RPN), Fishbone Diagram, and internal operational benchmarking. The results showed that the coating machine experienced 12 failure events with a total downtime of 1,110 minutes, an MTBF of 743.92 minutes/failure, an MTTR of 92.50 minutes/failure, and an Availability of 88.94%. Pareto analysis indicated that the blower, spray gun/nozzle, and coating drum contributed 81.08% of total downtime. FMEA identified the blower as the most critical component, with the highest RPN value of 384 and the largest downtime contribution of 390 minutes. Internal benchmarking between March and April showed a 45.83% downtime reduction, a 125.21% increase in MTBF, a 24.17% decrease in MTTR, and a 10.76 percentage-point increase in Availability. The proposed strategy emphasizes preventive and condition-based maintenance through airflow inspection, filter cleaning, motor temperature monitoring, nozzle cleaning, control panel calibration, and coating drum inspection. This study contributes by providing a structured reliability-based maintenance priority framework for pharmaceutical coating machine operations.